IMPLEMENTASI BOX MODELING DAN CONTORING MODEL PADA ANIMASI MERAKIT PC MENGGUNAKAN 3DSMAX - Belalawe, Benyamin Jago; Belalawe, Mateus Mas (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2020)
Current technological developments, especially in the 3D field experienced a lot of progress. 3D Modeling is the process of creating 3D objects that want to be expressed in a real visual form, both in the shape, texture and size of the object. Making 3D models of objects or objects using a computer to make objects look more alive and in accordance with the original object. The method applied in PC assembly animation is the Modeling Box and Contoring Model using 3DSMax. The results of this study can provide a picture for beginners in assembling a PC.